Transparency and Financing Choices of Family Firms - Ahmad, Muhammad Ishfaq; Naeem, Muhammad Abubakr; Hasan, Mudassar; Naseem, Muhammad Akram; Rehman, Ramiz Ur (Scientific Research, 2018)
Past literature indicates that family firms were different from nonfamily firms in term of performance, governess and disclosure. But there was very little evidence which specified the financial structure of family firm. Maturity and leverage, two proxies are used to examine the financial structure of family firm in this particular study. This study shows that family firms are different from non-family firms in terms of debt maturity and leverage. Moreover, transparency is negatively related to maturity which indicates that more transparency decreases maturity, while family firms have more debt maturity which suggested that family firms are more relying on long-term debt and there is a chance of expropriation in family firms due to less transparency. Furthermore, transparency is positively related with leverage which indicates that more transparency increases leverage, while family firms also have positive relationship with leverage which specifies that more transparency leads family firms’ financial structure more toward debt.
Keywords: Family Firms; Non-Family Firms; Maturity; Leverage